Novelist as a Vocation - Haruki, Murakami (Vintage, 2024)
One of Japan's most beloved contemporary novelists, internationally best-selling author Haruki Murakami discusses his life, writing process, and the sources of inspiration that have fueled his fantastical stories. Novelist as a Vocation is a revealing self-portrait comprising eleven essays that seek to answer long-burning questions behind a literary mind that has charmed and captivated readers around the world.